Kompetensi Aparatur Desa dan Akuntabilitas Pengelolaan Dana Desa dengan Partisipasi Masyarakat dan Komitmen Organisasi sebagai Variabel Moderasi - Jati, I Ketut; Dwirandra, Anak Agung Ngurah Bagus; Widhiyani, Ni Luh Sari; Kresnandra, Anak Agung Ngurah Agung (E-Jurnal Akuntansi; Vol 33 No 2 (2023)DO - 10.24843/EJA.2023.v33.i02.p15, 2023)
The study aims to determine the influence of village apparatus competence on village fund management accountability moderated by contingency factors, some of which are community participation and organizational commitment. The study population was village apparatus in Buleleng Regency in 129 villages, and the sample was selected using a purposive sampling technique so that around 30 villages met the criteria with a total of 120 respondents. Primary data was collected by distributing questionnaires to the sample. Test analysis using moderation regression analysis technique (MRA). The results of the study indicate that the competence of village apparatus has a positive effect on the accountability of managing village funds; Community participation weakens the influence of village apparatus competence on village fund management accountability; Organizational commitment strengthens the influence of village apparatus competence on village fund management accountability; The internal control system weakens the influence of village apparatus competence on village fund management accountability; Clarity of budget targets strengthens the influence of village apparatus competence on village fund management accountability. Keywords: Competence; Accountability; Community Participation; Organizational Commitment